Patient-reported outcome measures after mitral valve repair: a comparison between minimally invasive and sternotomy. (30th November 2020) - Whiteley, Jennifer; Toolan, Caroline; Shaw, Matthew; Perin, Giordano; Palmer, Kenneth; Al-Rawi, Omar; Modi, Paul
Abstract: OBJECTIVES: To compare patient-reported outcome measures of minimally invasive (MI) to sternotomy (ST) mitral valve repair. METHODS: We included all patients undergoing isolated mitral valve surgery via either a right mini-thoracotomy (MI) or ST over a 36-month period. Patients were asked to complete a modified Composite Physical Function questionnaire. Intraoperative and postoperative outcomes, and patient-reported outcome measures were compared between 2 propensity-matched groups ( n = 47/group), assessing 3 domains: 'Recovery Time', 'Postoperative Pain' (at day 2 and 1, 3, 6 and 12 weeks) and 'Treatment Satisfaction'. Composite scores for each domain were subsequently constructed and multivariable analysis was used to determine whether surgical approach was associated with domain scores. RESULTS: The response rate was 79%. There was no mortality in either group. In the matched groups, operative times were longer in the MI group ( P < 0.001), but postoperative outcomes were similar. Composite scores for Recovery Time [ST 51.7 (31.8–62.1) vs MI 61.7 (43.1–73.9), P = 0.03] and Pain [ST 65.7 (40.1–83.1) vs MI 79.1 (65.5–89.5), P = 0.02] significantly favoured the MI group. Scores in the Treatment Satisfaction domain were high for both surgical approaches [ST 100 (82.5–100) vs MI 100 (95.0–100), P = 0.15]. The strongest independent predictor of both faster recovery parameter estimate 12.0 [95% confidence interval (CI) 5.7–18.3, P < 0.001] and less pain parameter estimate 7.6 (95% CI 0.7–14.5, P = 0.03) was MI surgery. CONCLUSIONS: MI surgery was associated with faster recovery and less pain; treatment satisfaction and safety profiles were similar. Abstract : Median sternotomy (ST) used to be the most frequent surgical approach for mitral valve disease but, in the last 25 years, minimally invasive (MI) approaches (minithoracotomy) have rapidly increased due to reports of excellent outcomes at high-volume centres worldwide.